Identifying freshwater wetland suitable habitat through a hydrological-biological connectivity framework: A case study of Naoli River wetlands, China - Daiji Wan; Jian Yang; Xuan Liu; Qiwei Liu; Baolong Chen; Yanhui Chen; Dandan Zhao; Jiping Liu (Ecological Indicators)
Changes in hydrological connectivity not only interfere with the material transfer and energy flow processes within wetland ecosystems or between wetland ecosystems and other ecosystems but also pose potential risks to the ecosystem service functions of wetlands, such as water conservation, climate regulation, and biodiversity maintenance. It is essential to clarify the impacts of changes in hydrological connectivity on wetland habitats to restore wetlands and maintain species diversity. Explaining the effects of changes in hydrological connectivity on wetland habitats is crucial to restoring wetlands and maintaining species diversity. In this paper, we assessed hydrological connectivity and its impacts on wetland habitats based on geostatistical connectivity function and the biohydrological adaptation thresholds of the Naoli River wetland. The results showed that (1) the hydrological connectivity of wetlands within the Naoli River Reserve showed a fluctuating and decreasing trend, and the maximum distance difference between the high and low connectivity periods was 26 km. (2) Waterbirds and macroinvertebrates had a larger area of suitable habitat at moderate hydrological connectivity. At the same time, fish and phytoplankton showed a decrease in the area of suitable habitat with decreasing hydrological connectivity. (3) Hydrological connectivity significantly regulates a high-suitability habitat, and suitable hydrological connectivity increases habitat area by about 35 %. (4) The restoration of hydrological connectivity and suitable habitats should be emphasized in the Trans-Qixing River area, and wetland biodiversity should be maintained according to the hydrological connectivity status in the mainstream area of the Naoli River and the Inner-Qixing River area.